2009
DOI: 10.2217/pgs.09.5
|View full text |Cite
|
Sign up to set email alerts
|

Physiogenomic Analysis of the Puerto Rican Population

Abstract: Aims-Admixture in the population of the island of Puerto Rico is of general interest with regards to pharmacogenetics to develop comprehensive strategies for personalized healthcare in Latin Americans. This research was aimed at determining the frequencies of SNPs in key physiological, pharmacological and biochemical genes to infer population structure and ancestry in the Puerto Rican population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Admixed populations may differ from other populations in frequency, distribution, and combination of allelic variants in the genome [8]. Hispanics in the United States are a case of admixture, with mainly a trichotomous ancestral contribution of the following distant parental populations: Europeans, Native Americans, and West-Africans [7, 9, 10]. Using principal component analysis of autosomal genotype data in Hispanics and other putative ancestral populations, a tri-hybrid admixture pattern was confirmed by Bryc and coworkers [11].…”
Section: Introductionmentioning
confidence: 99%
“…Admixed populations may differ from other populations in frequency, distribution, and combination of allelic variants in the genome [8]. Hispanics in the United States are a case of admixture, with mainly a trichotomous ancestral contribution of the following distant parental populations: Europeans, Native Americans, and West-Africans [7, 9, 10]. Using principal component analysis of autosomal genotype data in Hispanics and other putative ancestral populations, a tri-hybrid admixture pattern was confirmed by Bryc and coworkers [11].…”
Section: Introductionmentioning
confidence: 99%
“…The highly admixed structure and trichotomous ancestry of Puerto Ricans was early described by our group, after analyzing data from an array of 384 SNPs in 222 cardiometabolic and neuroendocrine genes [14,15]. The analysis revealed that each subject in the Puerto Rican population was a ‘genetic mosaic’, with contributions from each of these three clusters (i.e., Caucasians, Africans and Amerindians), but in widely different proportions.…”
Section: Introductionmentioning
confidence: 99%
“…This admixture pattern gives rise to many combinatorial genotypes that impacts important pharmacological, biochemical and physiological pathways. Since such a rich repertoire of combinatorial genotypes is not present in traditional studies with more homogenous populations, we strongly believe that admixed populations (e.g., Hispanic Puerto Ricans) have the potential to be a better resource to develop DNA-guided algorithms for the treatment of different medical conditions [14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have published a physiogenomic analysis to infer structure and ancestry in the Puerto Rican population [21]. The Puerto Rican sample was found to be broadly heterogeneous, with three main clusters reflecting the historical admixture from Amerindian, African, and European ancestors.…”
Section: Introductionmentioning
confidence: 99%